The patterns of head and neck tumours in Northern Ghana: a histopathological review in a tertiary referral hospital in Northern Ghana - Der, Edmund M.; Antwi, Kwadwo F.; Adjeso, Theophilus J. K. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: There is paucity of published data on head and neck tumours (HNTs) in Ghana, even the few studies available were conducted in the middle and southern belts of the country. The present study in northern Ghana, was conducted to study the histopathological characteristics of HNTs and offer recommendations. Methods: This retrospective study analysed HNTs for the past 10 years at the Tamale Teaching Hospital in northern Ghana. Results: There were 576 HNTs, with 66.0% benign and 34.0% malignant. The mean age (years) was 34.9±21.6. Females were commonly affected 53.6%. Benign tumours were diagnosed in relatively young patients with mean age of 29.6±19.2, compared to 44.9±22.6 for the malignant tumours. Patients commonly present late with HNTs. The common anatomical sites were: odontogenic and maxillofacial bone (18.4%), oral cavity and mobile tongue (18.1%), and hypopharynx and larynx (13.9%). The histopathological subtypes were: squamous papilloma (13.9%), squamous cell carcinoma (SCC) (12.8%), and salivary gland pleomorphic adenoma (9.4%). The common benign tumours were; squamous papilloma (21.1%), salivary glands pleomorphic adenoma (14.2%), and benign vascular tumours (13.9%). For malignant tumours the order was; SCC (37.8%), lymphoma (11.2%) and olfactory neuroblastoma (10.2%). A significant number of patients had no history of cigarette smoking (p<0.0001). Conclusions: Benign tumours were the common neoplastic lesions within the head and neck region. HNTs were common in relatively young patients and in females. Benign tumours were diagnosed in relatively young patients compared to malignant tumours. Patient with malignant tumours presented early to health facilities, compared to those with benign tumours.